Interjection et procédure interpellative en grammaire interactionnelle : de l’image de soi à l’« allogénèse » ? - Laurent Fauré (Corela)
This paper offers to reconsider the calling from a distance as public activity, caught in the course-of-interaction. The case of French calling interjections hé and ho, allows to notice that interpellative forms are not specialized : they rather would constitute a beam of discursive and praxeological data. These one produce together a salient picture of the other as summoned participant. These units instantiate an in progress addressee in a allogenetic process. One will postulate that these units are multimodal resources orientated in speech which lie on a instructional basic value. Our approach is in line with interactional grammar : we adopt on the one hand several interactionists’ paradigms such Goffman’s proposals of the demeanor in public or conversationalist grounds and, on the other hand, praxematics hypothesis about formatting intersubjectivity. Our corpus makes a set of « colloquial » calling vocalizations uttered in public or in institutional situations ; it groups together taped-on and transcribed data, taken from various contexts : mediatized political meeting, working-activities, soccer training, tv or online programs showing off mediatic and cultural debate, or entertainment one’s.